2023
DOI: 10.1111/acer.15041
|View full text |Cite
|
Sign up to set email alerts
|

Chronic alcohol consumption and COVID‐19 infection risk: A narrative review

Abstract: During the COVID‐19 pandemic, many potential risk groups have been identified, such as those with obesity, diabetes, preexisting organ injuries, and several other conditions. Smoking is the most reported substance use disorder linked to increased COVID‐19 hospitalization rate and disease severity. In relation to smoking, we discuss the impairment of the innate and the adaptive immune systems as being among the main potential reasons for increased COVID‐19 infection risk and severity. Chronic alcohol consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 148 publications
0
9
0
Order By: Relevance
“…Outside of human studies, inhaled ethanol has also been shown in mouse models to protect against lethal influenza infection when delivered prophylactically ( 20 ). In contrast to these beneficial effects reported with topical airway administration via inhalation, heavy, prolonged oral alcohol misuse has been typically associated with immune suppression and worse infection outcomes ( 7 , 23 ). Collectively, these data suggest that the route of administration, dose, and duration of exposure play critical roles in modulating ethanol’s potential beneficial or negative effects on the human body.…”
Section: Discussionmentioning
confidence: 99%
“…Outside of human studies, inhaled ethanol has also been shown in mouse models to protect against lethal influenza infection when delivered prophylactically ( 20 ). In contrast to these beneficial effects reported with topical airway administration via inhalation, heavy, prolonged oral alcohol misuse has been typically associated with immune suppression and worse infection outcomes ( 7 , 23 ). Collectively, these data suggest that the route of administration, dose, and duration of exposure play critical roles in modulating ethanol’s potential beneficial or negative effects on the human body.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies that have demonstrated that alcohol consumption was considerably increased during the COVID-19 pandemic, which may increase the risk of depression, anxiety, stress, and other lifestyle factors in daily routines [84]. Substantial studies have also provided evidence that chronic alcohol consumption and alcohol use disorder have increased the risk of COVID-19 infection and severe disease progression [85].…”
Section: Discussionmentioning
confidence: 99%
“… 24 , 25 However, different clusters were observed during the pandemic, with decreased and increased alcohol consumption or no change in drinking behaviour. 26 , 27 Most worrisome was the situation for patients with AUD, as governmental regulations such as lockdowns restricted access to ongoing therapy for extended periods, with unpredictable impact on further disease progression. Hence it is suggested that a lockdown represents a risk factor for increasing alcohol consumption in people with AUD and relapse for those who were previously abstinent.…”
Section: What Has the Recode Consortium Achieved In The First Funding...mentioning
confidence: 99%